Performance of an Effective IOT Enabled Smart System with MQTT Protocol - et. al., P.Venu Madhav, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research proposes the internet of things (IoT) with controlling of Energy efficient network with help of DALI network. The DALI network design, works with help of MQTT protocol for high security. Here we are using small-scale controllers like Raspberry Pi, esteem viable contraptions can be utilized to degree detecting unit realities and in addition send it on line. Moreover, DALI (Digital Addressable Lights Interface) is an ultra-present day component of interaction in some of the electric apparatus and further, more a web server or PC on the way to cause a powerful notoriety of a sharp matrix. This work covers the communication of DALI people group of gathering of lighting installations with Raspberry Pi (specialist) over MQTT (Message Queuing Telemetry Transport) approach protecting the possibility of IOT inside the lower back of-the-scenes. Here we are using Controlling techniques for controlling all types of switching devices with help of web page.